Pemanfaatan Hidrofobik Deep Eutectic Solvents dalam Penyisihan Dimetoat, Klorpirifos, dan Profenofos pada Buah Tomat dan Sayur Brokoli - Daely, Axel Try Iddo; Manurung, Renita (Jurnal Teknik Kimia USU, 2020)
Organophosphate insecticide is a type of pesticide that is commonly used, where this pesticide can be toxic to environmental organisms even to humans. Hydrophobic Deep Eutectic Solvent (DES) is a new generation nonpolar solvent of ionic liquids because it has better physical properties and chemical properties so that it can be used in the extraction process. DES was synthesized at 50 oC for 15 minutes with a stirring speed of 300 rpm and a molar ratio of Dl-menthol: lauric acid varied from 1: 1, 2: 1, and 3: 1. Pesticide removal is done by mixing 5 ml of DES with 200 ml of aquadest and then Tomatoes and Broccoli vegetables are washed with the solution. DES characteristics are done by analyzing the shape and measuring the freezing point, density and viscosity of DES. The concentration of pesticide residues was analyzed using Gas Chromatography-Mass Spectrometer (GC-MS). The highest elimination of pesticides obtained with DES hydrophobic which has a molar ratio of dl-menthol: lauric acid is 3: 1 where the highest elimination of pesticides in Tomatoe is 44.82% for Dimethoate pesticide, 84.1% for Chlorpyrifos pesticide, and 83.72% for Profenofos pesticide and Broccoli 35.19% for Dimetoat pesticide, 64.64% for Chlorpyrifos pesticide, and 55.28% for Profenofos pesticides.